A Comparative Analysis of Traffic Nosie Levels in Basra City: during and before the Lock-down caused by Corona-virus Pandemic - Al-Hassen, Shukri I.; Madhloom, Farhan D. (Al-Adab Journal, 2021)
This study captured a rare opportunity to prove its hypothesis. This coincides with the imposition of a full ban on traffic in Basra City during March 2020 as a measure to prevent the Coronavirus pandemic that has recently spread throughout the country. Accordingly, measurements of traffic noise and noise dose during the referred period were made and the results were compared with a previous baseline study carried out in the same area in 2018. The same measurement equipment and method was used and the same measurement points were selected, in order to achieve the greatest accuracy and validity of comparison. The comparative analysis of the results showed that there is a significant difference in the traffic noise measurements between the baseline study and the present study, as a result of heavy traffic in the first and stopping in the second. The variance ratio was 32% in the case of noise levels and 99% in the case of noise dose. The results indicate that the spatial variation in noise pollution has decreased between the areas of the present study due to the absence of the influencing factor represented by traffic and the disruption of human activity. In addition, the noise dose is a reliable indicator for assessing the severity of susceptibility to noise, rather than the conventional noise-level scale only. It can be said, in general, that the Coronavirus pandemic sometimes has indirect positive effects on the environment despite its extreme danger to human health.